The Status of Northern Ireland after Brexit: Probable Models - Rudko, Serhii (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article highlights one of the main issues related to the UK's withdrawal from the European Union, Northern Ireland’s new status, in particular, the status of the border between NI and the Republic of Ireland. It has been an ‘apple of discord’ from the first stage and during the last stage of the Brexit negotiations. The future ‘hard’ or ‘soft’ Irish-British border is not a problem in the negotiations between the United Kingdom and the European Union only, but is also a serious domestic political challenge for Theresa May’s government. The article explains possible models of the future status of Northern Ireland. The most probable solutions are: a ‘reverse Greenland’, a ‘reverse Cyprus’ and a ‘German version’. Following the Good Friday Agreement of 1998, the EU invested heavily in supporting border communities for the development of small business and industry, which improved the economic situation in the area of the former conflict and facilitated border dialogue. However, it led to the fact that many enterprises were oriented towards the EU market or border trade. The article concludes that the ‘reverse Greenland’ model would enable Northern Ireland to remain in the single market and customs union apart from the rest of Great Britain, which would prevent the establishment of a tight boundary between both Irelands. The author outlined the possible implications of the ‘reverse Cyprus’ model, which suggests that the United Kingdom would technically remain a part of the EU, and that the EU’s legislation would be suspended only on its separate parts (that is, Wales and England). The researcher emphasizes that the ‘German version’ could be applied in the case of future reunification of both Irelands, then Northern Ireland would remain a part of the EU until its new status on the referendum have been resolved. The article summarized that no examples above provide a precise analogy, since Brexit is unprecedented event. The most likely models of the Northern Ireland’s future are the ‘reverse Greenland’ and the ‘reverse Cyprus’